Patient presentation, differential diagnosis, and management of penile lesions - Chipollini, Juan; De la Rosa, Alfredo Harb; Azizi, Mounsif; Shayegan, Bobby; Zorn, Kevin C.; Spiess, Philippe E. (Canadian Urological Association Journal, 2019)
N/A